Digital Devices and Cognitive Functions in Children - George A. Karkashadze; Leyla S. Namazova-Baranova; Elena A. Vishneva; Natalia Е. Sergeeva; Tinatin Yu. Gogberashvili; Nadezhda A. Ulkina; Elena V. Kaytukova; Dmitriy S. Kratko; Svetlana E. Kondratova; Safarbegim Kh. Sadilloeva; Marina A. Kurakina; Anastasiya I. Rykunova; et al. (Вопросы современной педиатрии, 2022)
The other contributors confirmed the absence of a reportable conflict of interests The influence of dynamically changing habits associated with the use of digital devices (DD) on the child’s brain is one of the most topical issues of the last decade. Ambiguous or contradictory data on this issue indicate the need of systematizing all the results of scientific research. This analysis shows negative effect of large amount of screen time on the development of children at early age, their academic performance, and attention at older ages due to media absenteeism, as well as the correlation between the use of digital devices with delayed reward. It is necessary to update and to conduct qualitative research to understand the issue in more comprehensive way.